A produção de efeitos de realidade em narrativas de filmes publicitários: análise de estratégias em segmentos de bebidas, no Brasil - Salbego, Juliana Zanini (2008)
In times of mediatic way of life, mankind s experience is more and more mediate by technological devices of communication. In this view, audiovisual publicity is social contest s product, an enunciative device in which strategies are made with a view to persuade the public about the discursive true that this publicity ensures. For such, in its ways to say and show, the advertisement must do the spectator to feel him or herself connected to the text, using elements that refer to realities. In this sense, this work aims to bring to the top its purposes throughout broking significant chains of audiovisual advertising texts, finding out trough which strategies the advertisement creates effects of sense of reality. For that, I use Discourses Semiology theory, observing the deal of sense production s strategies and the articulation of subjects in this process. I also use audiovisual languages theories, trying to comprehend the process of organization of its internal elements and such visual grammar. It s known that advertising discourses process elements that can take memories to the spectator, the sensation of a particular reality. The audiovisual narratives process resources of the iconic, of the verbal and of the sonorous able to stimulate the senses producing sensations throughout synesthesia processes, closed plans languages utilization, maximization of sound resources among other strategies.